Pemanfaatan Blog sebagai Media Pembelajaran B. Indonesia pada Kelas 5 SD/MI - Achmad Syaichun, Elok Faiqoh; Sabilla Faqih, Mery (Jurnal Gentala Pendidikan Dasar, 2022)
This modern era is determined by the rapid development of technology information, this also has an impact on the education sector. Internet has become an alternative way to search for all kinds of information needed by teachers and students, there is no space limit and time for this type of technology, the teaching and learning process becomes more flexible, teachers and students can find themselves outside classes and regular time schedules, especially students now already familiar with technology, they bring gadgets inside class, sometimes, they use it for their business alone, when the teacher is explaining something, the teacher must be creative facilitate not only the demand for internet technology and also to improve the teaching of the learning process, here The author proposes blogs as an alternative media, With this media, students can explore the posted material by the teacher on the blog. Students can study anywhere and anytime. which is certainly very different from conventional learning. Blog is one of the technology-based learning media Information and Communication (ICT). By using blog media expected to create active learning, creative, effective and fun. Use of blogs as media learning has the advantage of readily available information broad, fast, and precise, there is convenience in the learning process and technology support to facilitate the learning process teach. The application of ICT also has a distinctive advantage, namely that it does not limited by place and time.